2016
DOI: 10.5325/transportationj.55.3.0282
|View full text |Cite
|
Sign up to set email alerts
|

Full Steam Ahead: Firms in the US Economy Adjust Inventory for Changes in Transportation Costs But Not the Reverse

Abstract: Logistics theory suggests that transportation and inventory policies are jointly considered by managers because these costs have offsetting properties. For example, when inventory is ordered less frequently, total transportation costs are likely to be lower due to economies of scale; yet inventory carrying costs are likely to be higher. This research analyzes aggregate transportation and inventory costs in the United States from 1960 to 2013, finding that, in the US economy as a whole, inventory and transporta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The BLS’s methodology ensures both data reliability and consistency over time (Bureau of Labor Statistics 2019a), and the BLS’s resources far exceed the resources available for academics. Third, industry‐level results are more generalizable for shippers, which aligns with Swanson et al’s (2016, p. 284) statement, “One advantage of aggregation techniques is that results and models are more generalizable, a benefit unavailable with disaggregated data.” Lastly, our theorizing postulates mechanisms that are predicted to operate on an aggregate industry‐level basis. Consequently, our variables should be measured at the industry level to match our data to our theorizing (Miller et al 2018).…”
Section: Theory and Hypothesis Developmentsupporting
confidence: 77%
See 3 more Smart Citations
“…The BLS’s methodology ensures both data reliability and consistency over time (Bureau of Labor Statistics 2019a), and the BLS’s resources far exceed the resources available for academics. Third, industry‐level results are more generalizable for shippers, which aligns with Swanson et al’s (2016, p. 284) statement, “One advantage of aggregation techniques is that results and models are more generalizable, a benefit unavailable with disaggregated data.” Lastly, our theorizing postulates mechanisms that are predicted to operate on an aggregate industry‐level basis. Consequently, our variables should be measured at the industry level to match our data to our theorizing (Miller et al 2018).…”
Section: Theory and Hypothesis Developmentsupporting
confidence: 77%
“…In doing so, we make a practical contribution by providing empirical evidence validating statements by Smith (2018b) while also making a theoretical contribution per Makadok et al’s (2018) claim that offering new mechanisms to explain empirical effects is one way for scholars extend theory. Furthermore, our focus on articulating industry‐level mechanisms aligns with calls for logistics scholars to conduct more analyses using data at a higher level of aggregation than the firm (e.g., industry level and economy wide) to devise a more holistic understanding of important phenomena (Swanson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our wage turnover prediction can also be contrasted with research on between-industry differences in turnover rates, where evidence has consistently shown that industries with higher average wages tend to have lower turnover rates (Krueger and Summers 1988). This illustrates the utility of examining logistics topics longitudinally at a macrolevel (Swanson et al 2016).…”
Section: Introductionmentioning
confidence: 84%